Interview with Carlos Walter Porto-Gonçalves - Paulo Cesar Scarim (Geografares, 2023)
Interview by Carlos Walter Porto-Gonçalves given to Paulo Cesar Scarim in August 1999 as part of his master’s thesis and is in the annex to the dissertation, as well as the other interviews.